BUSINESS SUSTAINABILITY STRATEGIES OF AGRIBUSINESS MSMEs IN THE NEW NORMAL ERA - Khomah, Isti; Kusnandar, Kusnandar; Harisudin, Mohamad; Adi, R. Kunto; Qonita, Rr. Aulia; Setyowati, Nuning; Riptanti, Erlyna Wida (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2022)
This research aims to determine internal and external factors, formulate strategies, and decide the priority of agribusiness MSME sustainability strategies in Sukoharjo Regency in the new normal era. This research uses basic descriptive and analytical methods. A total of 28 key informants were selected purposively. Data collection was completed through in-depth interviews. Data were analyzed using the IFE, EFE, IE, SWOT, and QSP matrices. The research results depict that the most essential strength is the support of experienced human resources with particular specialties and the most significant weakness is the limited business capital. Meanwhile, product diversification becomes the biggest opportunity and a decrease in production due to the COVID-19 pandemic serves as the most challenging threat. The IE matrix demonstrates that the position of agribusiness MSMEs in Sukoharjo Regency is in cell V, which means keeping and maintaining that can be done with product penetration and development strategies. Alternatives to agribusiness MSME sustainability strategies are building synergies to increase market share with online marketing; improving the quality of human resources through training; establishing partnerships with suppliers to suppress raw materials; strengthening quality control to maintain quality; innovating the product; maximizing the ability of human resources and the management of product competitiveness; introducing, promoting, and discounting products; and increasing partnerships with large businesses. In the new normal era, the priority of agribusiness MSME business sustainability strategy in Sukoharjo Regency is building synergies to improve the market with online marketing.